Challenging measles case definition: three measles outbreaks in three Health Regions of Portugal, February to April 2018 - Augusto, Gonçalo Figueiredo (2019)
Free PMC Article: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6152152/